Reduction of Friction of Metals Using Laser-Induced Periodic Surface Nanostructures - Zhuo Wang; Quanzhong Zhao; Chengwei Wang (Micromachines, 2015)
We report on the effect of femtosecond-laser-induced periodic surface structures (LIPSS) on the tribological properties of stainless steel. Uniform periodic nanostructures were produced on AISI 304L (American Iron and Steel Institute steel grade) steel surfaces using an 800-nm femtosecond laser. The spatial periods of LIPSS measured by field emission scanning electron microscopy ranged from 530 to 570 nm. The tribological properties of smooth and textured surfaces with periodic nanostructures were investigated using reciprocating ball-on-flat tests against AISI 440C balls under both dry and starved oil lubricated conditions. The friction coefficient of LIPSS covered surfaces has shown a lower value than that of the smooth surface. The induced periodic nanostructures demonstrated marked potential for reducing the friction coefficient compared with the smooth surface.